Endoscopic Management as a Viable Therapy for Pancreaticopleural and Pancreaticopericardial Fistulas. Issue 1 (15th January 2021) - Chan, Sandy; Petersile, Matthew; Churrango, Gustavo; Zivny, Jaroslav
ABSTRACT: Pancreatic fistulas are rare complications of chronic pancreatitis, typically caused when disruption of the pancreatic duct causes leakage of pancreatic fluid that erodes through neighboring organs and structures. Pancreatic fistulas to the pericardium and pleural spaces are extremely rare, and cases of multiple fistulas tracking from the pancreas have not been reported before. Management of these fluid collections is challenging with no consensus described in the current literature. We report a case of a patient with concurrent pancreaticopericardial and pancreaticopleural fistulas who improved with endoscopic management.